Determining pigment extraction efficiency and pigment stability of dragon fruit (Hylocereus polyrhizus) - Rebecca, O.P.S.; Zuliana, R.; Boyce, A.N.; Chandran, S. (Asian Network for Scientific Information, 2008)
Pigment extracted from the pulp of Hylocereus polyrhizus showed a difference in colour when subjected to room temperature extraction and 110°C extraction. The room temperature extraction yielded red-purple coloured pigments while the 100°C extraction yielded scarlet red coloured pigments. Experiments were carried out to investigate the best water:weight ratio and optimum temperature to obtain highest pigment concentration, best extraction method and best storing condition. Best water:weight ratio was 1:1, best temperature observed was 100°C, best extraction method was by using juice concentrate rather than water extraction and the best storing condition was storage in -20°C. Both extraction methods exhibited stable pH reading after one week of storage. Nevertheless, the best method to obtain high pigment concentration is by using juice concentrate which is at least two times more concentrated than samples extracted with water. © 2008 Asian Network for Scientific Information.